Feasibility Evaluation in Port Development: A Systematic Literature Review of Global Trends, Methodologies, and Risks - Wawan Rudi Berlianto; Dedi Purwana; Agus Wibowo (Journal of Management and Social Sciences, 2026)
Feasibility evaluation is a crucial step in port development as it ensures that the project to be implemented provides optimal technical, economic, social, and environmental benefits. This study aims to provide a comprehensive overview of global research trends related to port feasibility evaluation, approaches applied in previous studies, and risks that arise when feasibility aspects are neglected in port development. Using a systematic literature review (SLR) approach, the study analyzes articles published between 2020 and 2025 indexed in Scopus. The results show that there has been increasing global attention to the importance of sustainable ports focused on green technologies and terminal automation. However, many studies still overlook social and environmental risks in feasibility evaluations. The study also found that neglecting feasibility aspects can lead to economic losses, environmental damage, and social dissatisfaction, resulting in project failure. Therefore, this research emphasizes the need for a more integrated feasibility evaluation that includes all technical, economic, social, and environmental dimensions. This study is expected to contribute to the development of a more holistic feasibility evaluation model, especially for developing countries like Indonesia, which still face significant challenges in port modernization and the adoption of green technologies.